Investor disagreement: the modern approach - Barbosa, Fernando Ferreira da Luz (2015)
Disagreement between economists is a well know fact. However, it took a long time for this concept to be incorporated in economic models. In this survey, we review the consequences and insights provided by recent models. Since disagreement between market agents can be generated through different hypotheses, the main differences between them are highlighted. Finally, this work concludes with a short review of nowcasting using google trends, emphasizing advances connecting both literatures.